2015
DOI: 10.1111/1462-2920.12691
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics of Colwellia psychrerythraea at subzero temperatures – a life with limited movement, flexible membranes and vital DNA repair

Abstract: The mechanisms that allow psychrophilic bacteria to remain metabolically active at subzero temperatures result from form and function of their proteins. We present first proteomic evidence of physiological changes of the marine psychrophile Colwellia psychrerythraea 34H (Cp34H) after exposure to subzero temperatures (-1, and -10°C in ice) through 8 weeks. Protein abundance was compared between different treatments to understand the effects of temperature and time, independently and jointly, within cells transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 79 publications
(164 reference statements)
2
41
0
Order By: Relevance
“…Applying the log 2 FC (log base 2 Fold Change) of the transcriptome in the calculated model, the fluxome was modified and the metabolic pathway of E. antarcticum B7 started to produce short-chain fatty acids. This metabolic behavior has been experimentally documented for other cold-adapted bacteria [23,25]. …”
Section: Exiguobacterium Antarcticum B7 As a Model Organism For Stmentioning
confidence: 66%
See 2 more Smart Citations
“…Applying the log 2 FC (log base 2 Fold Change) of the transcriptome in the calculated model, the fluxome was modified and the metabolic pathway of E. antarcticum B7 started to produce short-chain fatty acids. This metabolic behavior has been experimentally documented for other cold-adapted bacteria [23,25]. …”
Section: Exiguobacterium Antarcticum B7 As a Model Organism For Stmentioning
confidence: 66%
“…In a genomic study of Colwellia psychrerytharea the proteins involved in the synthesis, ramification, and cis-isomerization of polyunsaturated fatty acids were described [22]. Subsequently, the authors identified differentially expressed genes of polyunsaturated fatty acid synthases ( pfaC , pfaA , and pfaD ) [23]. To date, these synthase enzymes have been described only in marine bacteria [23,24].…”
Section: Mechanisms Of Bacterial Adaptation To Coldmentioning
confidence: 99%
See 1 more Smart Citation
“…Endonuclease IV, the enzyme responsible for recognition and priming of the damaged site for repair in numerous bacteria (Hosfield et al ., ), is increased almost threefold in the two stressed conditions compared to 23°C (Table ). Several proteins involved in DNA repair were also detected at −10°C in Colwellia psychrerythraea (Nunn et al ., ). In addition to potential increases in DNA damage, low temperatures and stress conditions can induce changes to DNA supercoiling, and since DNA topology has a substantial impact on gene expression (Pruss and Drlica, ), mediating these changes would be expected.…”
Section: Resultsmentioning
confidence: 97%
“…halocryophilus . This work is only the second proteomic study performed at such a low temperature (–10°C) (Nunn et al ., ) and the first at −10°C for an organism isolated from permafrost. Given its wide growth range and ability to grow at subzero temperatures, gaining a better understanding of the mechanisms used by this bacterium for subzero growth is particularly interesting.…”
Section: Introductionmentioning
confidence: 99%